Effects of Palatal Expansion with Torque Activation using a Transpalatal Arch: A Preliminary Single-Blind Randomized Clinical Trial - Fataneh Ghorbanyjavadpour; Vahid Rakhshan (International Journal of Dentistry)
Purpose. The literature regarding the treatment of posterior crossbites using a transpalatal arch (TPA) is scarce. Moreover, there is only one clinical study on the correction of unilateral crossbites using torque activation. This is an important clinical issue; therefore, this study was conducted to show the effects of an active Goshgarian TPA in correcting nonfunctional single-tooth unilateral crossbite. Methods. The present single-blind, randomized clinical trial examined 60 observations on 30 individuals with nonfunctional single-tooth unilateral crossbites in the first permanent molar area. Patients were randomly divided into two groups of “symmetric expansion” [control] and “expansion + torque activation” using Goshgarian TPAs [experimental]. The palatal arch was expanded at a rate of 2 mm/month, for 2–8 months. The average treatment durations were 157.9 and 117.1 days, respectively, for the control and experimental groups. Dentoskeletal alterations were assessed on dental records, posteroanterior frontal cephalographs, and occlusal radiographs taken before and after treatment. Changes induced by treatments in each group and differences between changes in both groups were analyzed statistically (α = 0.05). Results. The treatment duration was significantly shorter in the experimental group (P<0.05). The extent of dental displacement on the crossbite side was significant no matter what treatment was applied (P<0.001); no between-group difference was detected (P>0.05). Both treatments tilted the teeth in crossbite (P<0.001) without any between-group difference (P>0.05). The noncrossbite molar was displaced in the control group, whereas this did not occur in the experimental group (between-group P<0.001). Conclusions. The Goshgarian TPA can be used with torque activation in order to deliver a more effective and faster correction of nonfunctional single-tooth unilateral crossbites with more favorable clinical results.